An Examination of Sassanian Siege Warfare (3rd to 7th centuries CE) - Farrokh, Kaveh (Faces of War, 2024)
This article examines Sassanian siege warfare and technology in the domains of ballistae, ‘scorpions’, catapults, and battering rams. Sassanian siege warfare necessitated the use of protection/shielding for personnel (combat troops, engineers, laborers), mounds, mining, scaling of walls, as well as the digging of ditches and trenches. Archery barrages played a seminal role in support of siege operations. The arteshtārān (lit. warriors; mainly paighan infantry, archers, and savārān cavalry) and pil-savār (elephant warriors/riders) would undertake combat operations with manual labour provided by peasant recruits. Battle elephants could also be used in siege operations (for example at Nisibis, 350 CE). The environmental element of water was utilised (for example during the sieges of Nisibis, 337 or 338 CE and 350 CE). Incendiary factors could also be weaponised in siege operations. In summary, Sassanian siege warfare capabilities appear to have achieved proficiency levels equivalent to contemporary Roman armies.